Explanations for the observed increase in fast electron penetration in laser shock compressed materials - Batani,D; Davies,JR; Bernardinello,A; Pisani,F; Koenig,M; Hall,TA; Ellwi,S; Norreys,P; Rose,S; Djaoui,A; Neely,D (Physical Review E Statistical Physics Plasmas Fluids and Related Interdisciplinary Topics, 2000)
We analyze recent experimental results on the increase of fast electron penetration in shock compressed plastic [Phys. Rev. Lett. 81, 1003 (1998)]. It is explained by a combination of stopping power and electric field effects, which appear to be important even at laser intensities as low as [Formula Presented] An important conclusion is that fast electron induced heating must be taken into account, changing the properties of the material in which the fast electrons propagate. In insulators this leads to a rapid insulator to conductor phase transition. © 2000 The American Physical Society.